Photothermal measurement of absorption and scattering losses in thin films excited by surface plasmons - Domené, Esteban Alejo (2009)
We present a novel noncontact, photothermal technique, based on the focus error signal of a commercial CD pickup head that allows direct determination of absorption in thin films. Combined with extinction methods, this technique yields the scattering contribution to the losses. Surface plasmon polaritons are excited using the Kretschmann configuration in thin Au films of varying thickness. By measuring the extinction and absorption simultaneously, it is shown that dielectric constants and thickness retrieval leads to inconsistencies if the model does not account for scattering.